"Cycling was never so easy!" An analysis of e-bike commuters' motives, travel behaviour and experiences using GPS-tracking and interviews. (December 2017) - Plazier, Paul A.; Weitkamp, Gerd; van den Berg, Agnes E.
Abstract: The market for electrically-assisted cycling is growing fast. When substituting motorized travel, it could play an important role in the development of sustainable transport systems. This study aimed to assess the potential of e-bikes for low-carbon commuting by analysing e-bike commuters' motives, travel behaviour and experiences. We GPS-tracked outdoor movements of 24 e-bike users in the Netherlands for two weeks and used their mapped travel behaviour as input for follow-up in-depth interviews. Most participants commuted by e-bike, alternated with car use. E-bike use was highest in work-related, single-destination journeys. It gave participants the benefits of conventional cycling over motorized transport (physical, outdoor activity) while mitigating relative disadvantages (longer travel time, increased effort). The positive experience of e-bike use explained the tolerance for longer trip durations compared to other modes of transportation. Participants were inclined to make detours in order to access more enjoyable routes. Results demonstrate that e-bikes can substitute motorized commuting modes on distances perceived to be too long to cover by regular bike, and stress the importance of positive experience in e-bike commuting. This provides impetus for future actions to encourage commuting by e-bike. Highlights: Motives, behaviour and experiences of 24 e-bike commuters were studied using GPS and interviews. E-bike choice was triggered by changes in work or home environment and perceived health benefits. Findings show that participants use their e-bike as a substitute for motorized commuting. Longer commuting times by e-bike were accepted in return for the benefits of assisted cycling. Participants were inclined to choose enjoyable routes over shorter routes.